2021
DOI: 10.1186/s12884-021-03873-8
|View full text |Cite
|
Sign up to set email alerts
|

Hospital discharge on the first compared with the second day after a planned cesarean delivery had equivalent maternal postpartum outcomes: a randomized single-blind controlled clinical trial

Abstract: Objective Determining the effect of discharge time after elective cesarean section on maternal outcomes. Methods This study is a randomized clinical trial that performed on 294 women who undergo elective cesarean section. The patients were randomized in two groups by simple randomization method: Group A (discharge 24 h after cesarean) and group B (discharge for 48 h after cesarean). In both groups, during the first 24 h, they received intravenous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
1
7
1
Order By: Relevance
“… 4 , 5 Length of hospital stay is becoming an area of interest for researchers worldwide, as it is a readily available health indicator reflecting hospital activity and is an indirect estimator of resource consumption and efficiency. 6 , 7 However, there is much debate on LoS and its duration after CD.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 Length of hospital stay is becoming an area of interest for researchers worldwide, as it is a readily available health indicator reflecting hospital activity and is an indirect estimator of resource consumption and efficiency. 6 , 7 However, there is much debate on LoS and its duration after CD.…”
Section: Introductionmentioning
confidence: 99%
“…This trend was attributed to increased rate of wound infection and deep vein thrombosis which was commoner among the control group. In a related study by Ghaffari et al in which women were allowed to go home on the first compared with the second day after a planned caesarean delivery, the maternal postpartum outcomes were found to be similar one week and 6 weeks postpartum [ 21 ]. Day 1 discharge might be difficult to advocate in the study area because of the pervading poor maternal and child healthcare services in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…A national register-based study in Denmark reported the length of hospital stay after CS significantly reduced from 97 hours (4.0 days) in 2004 to 58 hours (2.4 days) in 2016 [23]. Furthermore, enhanced recovery after surgery (ERAS) was proposed recently for cesarean deliveries and clinical outcomes and patients' recognition was comparable to the normal care [24,25]. Thus, further studies to validate the predictive value of postoperative CRP in outpatient clinical settings would be needed before applying the marker where early discharge is common.…”
Section: Plos Onementioning
confidence: 99%